Ruptures : anthropologies of discontinuity in times of turmoil - Holbraad, Martin; Kapferer, Bruce; Sauma, Julia (UCL Press, 2019)
Ruptures brings together leading and emerging international anthropologists to explore the concept of 'rupture'.